THE IMPROVEMENT OF STUDENT’S CONCEPT MASTERY IN ELECTROLYTE AND NON ELECTROLYTE SOLUTIONS AND REDOX REACTION THROUGH NUMBERED HEAD TOGETHER COOPERATIVE LEARNING MODEL - ayu karunia lestari; ratu betta rudibyani; chansyanah diawati (Universitas Lampung, 2012)
Abstract:The objective of this research is to describe effectiveness of Numbered Head Together (NHT) technique of cooperative learning model in improving electrolyte and non electrolyte solutions and redox reaction concept masteries. This research used quasi expewriment method with Non Equivalent Control Group Design. Population in this research was all Grade X students in YP UNILA senior High School in Bandar Lampung from classroom X1 to X11 in event semester of academic year 2011/2012. Samples were classroom X3 and X4 as experiment classrooms using NHT learning model. Samples were selected using purposive sampling. Clasroom X4was selected as control by using conventional learning.The results showed that N-gain average values of concept masteries in experiment and control classrooms were 0.599 and -0.477 respectively. The hypothesis test results showed that the classrooms with NHT technique of cooperative learning model had higher levels of activities and concept masteries compared to classroom with conventional learning. The conclusion of this research was that the NHT technique of cooperative learning model was effective in improving electrolyte and non electrolyte solutions and redox reaction concept masteries. Keywords: NHT technique of cooperative learning model, activity and concept mastery